Enabling technologies driving drug research and development - Vass, Panna; Akdag, Dara Sevkan; Broholm, Gabriel Enemark; Kjaer, Jesper; Humphreys, Anthony J.; Ehmann, Falk (Frontiers in Medicine, 2023)
ABSTRACT One of the strategic goals of the European Medicines Agency (EMA) and the European Medicines Regulatory Network is to support the research and uptake of innovative methods and technologies in the development of medicines. To promote this goal, EMA drew up a list of enabling technologies (ETs), which are novel and fast-growing technologies that have the potential to enable innovation and therefore exert considerable impact on drug development. In this work, enabling technologies identified by the EMA are analysed to measure their impact on drug development by following their journey from publications through early regulatory interactions to clinical trials between 2019 and 2022. This work also reviews the current list of EMA-identified ETs by scrutinising previously unseen innovative technologies identified in EMA submissions data. The analysis shows large variations in the appearance of the various innovative technologies in the different studied data sources, which provided valuable insights into the “Journey of Innovation” that innovative technologies undergo. Several emerging technologies were identified and endorsed for inclusion in the enabling technologies list, whereas some others already on the list were proposed to be excluded due to their low appearance in regulatory interactions as well as clinical trials and publications. Overall, this analysis highlights the relevance and value of continuously scanning and monitoring enabling technologies, supporting Europe’s goal to remain a leader in research and development of innovative technologies, methods, and methodologies relevant to drug development.